Two meals a day : the simple sustainable strategy to lose fat, reverse aging, & break free from diet frustration forever - Sisson, Mark, 1953-; Kearns, Brad, 1965- (Grand Central Publishing, 2021)
The health and fitness expert presents a comprehensive lifestyle approach to weight control based on the principles of intermittent fasting, explaining how to burn body fat while maintaining energy, focus, and a positive attitude.